Design and synthesis of carborane-containing estrogen receptor-beta (ERβ)-selective ligands. Issue 19 (1st October 2015) - Ohta, Kiminori; Ogawa, Takumi; Oda, Akifumi; Kaise, Asako; Endo, Yasuyuki
Graphical abstract: Abstract: Candidates for highly selective estrogen receptor-beta (ERβ) ligands (6a –c, 7a –c, 8a and8b ) were designed and synthesized based on carborane-containing ER ligands1 and2 as lead compounds. Among them, p -carboranylcyclohexanol derivatives8a and8b exhibited high ERβ selectivity in competitive binding assay: for example, 8a showed 56-fold selectivity for ERβ over ERα. Docking studies of8a and8b with the ERα and ERβ ligand-binding domains (LBDs) suggested that the p -carborane cage of the ligands is located close to key amino acid residues that influence ER-subtype selectivity, that is, Leu384 in the ERα LBD and Met336 in the ERβ LBD. The p -carborane cage in8a and8b appears to play a crucial role in the increased ERβ selectivity.